Correlation between oesinophilia and adrenocortical insufficiency in sepsis and septic shock - Farouk Mostafa Faris Mohammed; Marwa Sheta; Mohamed Elsafee; Rania Elhoseiny (Cairo : Farouuk Mostafa Faris Mohammed, 2010)
Sepsis and septic shock are associated with high rate of morbidity and mortality . In some cases septic shock refractory to IV fluids and vasopressors may be associated with adrenocortical insufficiency . Oesinophilia is assumed to be a marker of adrenocortical insufficiency . The study was performed to better define the incidence of adrenocortical insufficiency in sepsis and septic shock to clarify whether glucocorticoid supplementation is beneficial in patients with septic shock and its effect on mortality and to find whether oesinophilia may be used as a marker of adrenocortical insufficiency in sptic shock
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Adrenal insufficiency; Oesinophilia; Sepsis , septic shock